A type-2 fuzzy index to assess high heeled gait deviations using spatial-temporal parameters. Issue 2 (3rd February 2022) - Massoud, Rasha
Abstract: This paper introduces an intelligent index that numerically assesses high-heeled gait deviations. Experiments were conducted on 14 young female volunteers, and the spatial-temporal gait parameters were calculated at each heel height. A type-2 fuzzy system index was built using the baseline case (barefoot). The index showed sensitivity to heel height changes. Moreover, its values divided the heel heights used in this study into three groups, depending on their effect on the gait parameters. A high correlation between the proposed index and the gait profile score (GPS) was found, this supports the index validity to evaluate different human gait deviations.